Psychometric properties of the Italian version of the Experience in Close Relationship Scale 12 (ECR-12): an exploratory structural equation modeling study - Agostino Brugnera; Cristina Zarbo; Benedetto Farina; Angelo Picardi; Andrea Greco; Gianluca Lo Coco; Giorgio A Tasca; Samantha Carlucci; Adalberto Auteri; Francesco Greco; Angelo Compare (Research in Psychotherapy, 2019)
The Experiences in Close Relationship Scale (ECR) is one of the most commonly used self-report instruments of adult attachment and has been widely adopted in psychotherapy research. Composed of two subscales, namely Attachment Avoidance and Anxiety, the ECR was recently shortened to a 12-items version, called the ECR-12. Given the importance of extending knowledge on its applicability in understudied populations, our aim was to validate the ECR-12 in a large sample of Italian native-speakers. A total of 1197 participants (73.2% females; mean age=28.53±11.37 years) completed the ECR-12. Each participant also completed other measures of attachment, psychopathology, interpersonal distress, coping strategies, and well-being. An Exploratory Structural Equation Modeling analysis showed an excellent fit of the data, providing support for the two-dimensional orthogonal structure of the ECR-12. In addition, the measurement model was invariant across genders. Both attachment anxiety and attachment avoidance subscales demonstrated good internal reliability, with McDonald’s Omegas and Cronbach’s Alphas above the suggested 0.8 cut-off. Finally, the Italian version of ECR-12 showed adequate convergent, concurrent, and divergent validity. Highly anxious individuals reported the highest levels of maladaptive interpersonal functioning and coping strategies, resulting in lower well-being. Interestingly, both attachment insecurity dimensions predicted higher levels of psychopathology, even after controlling for demographic variables and levels of self-reported relational difficulties. Given the good psychometric properties of the ECR-12, researchers and practitioners in Italy are encouraged to adopt the ECR-12 in their future research on adult attachment in psychotherapy.